No Significant Association between the Alpha-2A-Adrenergic Receptor Gene and Treatment Response in Combined or Inattentive Subtypes of Attention-Deficit Hyperactivity Disorder - Park, S.; Kim, J.-W.; Kim, B.-N.; Hong, S.-B.; Shin, M.-S.; Yoo, H.-J.; Cho, S.-C. (Pharmacopsychiatry, 2013)
Given the shortage of pharmacogenetic studies on treatment response according to subtype of attention-deficit hyperactivity disorder (ADHD), we investigated the associations between the MspI and DraI polymorphisms of the alpha-2 A-adrenergic receptor gene (ADRA2A) and treatment response to methylphenidate according to subtype of ADHD.We enrolled 115 medication-naïve children with ADHD into an open label 8-week trial of methylphenidate. The participants were genotyped and evaluated using the Clinical Global Impression (CGI), ADHD rating scale, and Continuous Performance Test (CPT) pre- and post-treatment.There was no statistically significant association between the MspI or DraI genotypes and the relative frequency of CGI-improvement (CGI-I) 1 or 2 status among any of the groups (all types of ADHD, ADHD-C, or ADHD-I). However, among the children with ADHD-C, those subjects with the C/C genotype at the ADRA2A DraI polymorphism tended to have a CGI-I 1 or 2 status post-treatment (OR=4.45, p=0.045).The results of this study do not support the association between the the MspI or DraI genotypes and treatment response to methylphenidate in ADHD. However, our results suggest that subtypes might influence pharmacogenetic results in ADHD.·
Keywords: attention-deficit/hyperactivity disorder; ADRA2A; treatment response; subtype; methylphenidate